Holocene tephra from the Chukchi-Alaskan margin, Arctic Ocean: implications for sediment chronostratigraphy and volcanic history - Ponomareva, Vera; Vakhrameeva, Polina (Quaternary geochronology, 2018)
Developing chronologies for sediments in the Arctic Ocean and its continental margins is an important but challenging task. Tephrochronology is a promising tool for independent age control for Arctic marine sediments and here we present the results of a cryptotephra study of a Holocene sedimentary record from the Chukchi Sea. Volcanic glass shards were identified and quantified in sediment core HLY0501-01 and geochemically characterized with single-shard electron microprobe and laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS). This enabled us to reveal a continuous presence of glass shards with identifiable chemical compositions throughout the core. The major input of glasses into the sediments is geochemically fingerprinted to the ∼3.6 ka Aniakchak caldera II eruption (Alaska), which provides an important chronostratigraphic constraint for Holocene marine deposits in the Chukchi-Alaskan region and, potentially, farther away in the western Arctic Ocean. New findings of the Aniakchak II tephra permit a reevaluation of the eruption size and highlight the importance of this tephra as a hemispheric late Holocene marker. Other identified glasses likely originate from the late Pleistocene Dawson and Old Crow tephras while some cannot be correlated to certain eruptions. These are present in most of the analyzed samples, and form a continuous low-concentration background throughout the investigated record. A large proportion of these glasses are likely to have been reworked and brought to the depositional site by currents or other transportation agents, such as sea ice. Overall, our results demonstrate the potential for tephrochronology for improving and developing chronologies for Arctic Ocean marine records, however, at some sites reworking and redistribution of tephra may have a strong impact on the record of primary tephra deposition.
Gesehen am 23.04.2020